Study of optimization in mammography for thick breasts using different filtrations (Research, Society and Development, 2022)
Mammography is the gold standard exam for breast cancer screening, being recommended by the Brazilian Ministry of Health every 2 years for women aged 50 to 69 years. As there is a great demand in diagnostic imaging services and due to their clinical importance, quality control and the optimization process are indispensable tools to guarantee the quality of the mammography exam. The mammography unit evaluated in this work is limited, in automatic mode, to a maximum voltage of 30 kVp, causing damage to images of thick breasts, in which higher voltages are required to produce an image with diagnostic quality. Thus, the present study aimed to evaluate the contrast-to-noise ratio (CNR), mean glandular dose (MGD) and image quality, in an optimization process directed to the use of more energetic beams in thick breasts (equivalent to 7 cm of PMMA). The results showed that with the use of manual mode to increase the beam energy (32 and 35 kVp), the RCRrel was higher, consequently increasing the DGM. A downward trend in the Figure of Merit (FOM) was observed as the current-time product (mAs) increased sufficiently to meet the minimum national requirement. Regarding the image quality compared to the use of automatic mode, it was possible to observe a greater amount of microcalcification groups and fibers.